An evaluation toward the post-certification teacher performance in the natural history learning process for the elementary school degree - Azizah, Siti Noor; Suparwoto, Suparwoto; Nuryana, Zalik (Psychology, Evaluation, and Technology in Educational Research, 2020)
The study aims at describing the teacher performance in the Natural History Learning Process for the Elementary School Degree throughout the Province of Yogyakarta Special Region from the four competencies namely personality competency, professionalism competency, pedagogy competence and social competency based on the self-assessment, the principal assessment, the peer assessment, the student assessment and the observation toward the learning process after the certification. The nature of the study is an evaluative study using the descriptive quantitative approach. The study itself was conducted in both the Public Elementary Schools and the Private Elementary Schools throughout the Province of Yogyakarta Special Regions. The subjects of the study were the teachers who had been teaching Natural History in both schools who had passed the certification test in 2007 and 2008 and who had also been receiving the certification allowance. During the conduct of the study, the data gathering instruments that had been implemented were questionnaire, observation sheet and documentation. On the other hand, the data analysis technique that had been adopted was descriptive statistical analysis with percentage. Then, the results of the study show that the post-certification performance of Natural History teachers have been â€œVery Goodâ€ based on the personality, professionalism, pedagogy and social competency and also based on the results of the self-assessment, the principal assessment and the peer assessment. The details on the results of the post-certification teacher performance in this regard might be elaborated as follows: (1) personality competence 96.70%; (2) professionalism competence 76.40%; (3) pedagogy competence 83.30%; and (4) social competence 88.90%. Furthermore, the results of the student assessment assert that the post-certification of Natural History teachers belongs to the â€œVery Goodâ€ category with the assessment rate of 96.70%. Last but not the least, the results of the observation toward the teacher learning process also belong to the â€œVery Goodâ€ category with the following details: (1) pre-learning activities 93.30%; (2) core activities 93.30%; and (3) closing activities 73.30%.